Investigating Vitamin D Status: A Key Factor in Gestational Diabetes among Pregnant Women - Atiya K. Mohammed; Bushra Jabbar Hamarashid (Kufa Journal for Nursing Sciences)
Background: Vitamin D deficiency within the general population suggests the emergence of glucose intolerance. The relationship between insufficient vitamin D levels and gestational diabetes mellitus remains a subject of ongoing discussion.